Fashion DIY sebagai Ruang Empowerment: Analisis pada Akun TikTok @dillaprb - Caroline, Anak Agung Putri Tiara; Zuhri, Saifudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study analyzes empowerment messages in Do It Yourself (DIY) fashion content on the TikTok account @dillaprb using qualitative content analysis of five selected videos. The analysis focuses on three aspects: pragmatic, semantic, and syntactic. Findings reveal that the creator’s content goes beyond showcasing the sewing process, as it also delivers atomistic empowerment through information, motivation, and inspiration that encourage active audience participation. Pragmatically, the creator builds emotional closeness through personal greetings, creative exploration, and practical tips. Semantically, the messages emphasize self-expression, personal identity, and creative freedom. Syntactically, the content features casual language, code-switching, and interactive communication styles. Overall, @dillaprb’s success in fostering engagement lies in integrating meaning, language structure, and communication strategies, thereby creating an inclusive, inspiring, and collaborative creative space.